Nickel Metal Hydride Batteries 2017 - Kwo Young (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book contains twenty papers focusing on research investigations in the field of nickel/metal hydride (Ni/MH) batteries in 2017. These papers summarize the joint efforts in Ni/MH battery research from BASF, Wayne State University, Michigan State University, FDK Corp, Institute for Energy Technology, Central South University, University of Science and Technology Beijing, Zhengzhou University of Light Industry, Inner Mongolia University of Science and Technology, Shenzhen Highpower, and University of Witwatersrand from 2016-2017 through reviews of active materials, previous academic publications, issued EU Patents and filed Chinese Patent Applications, descriptions of current research results in advanced components and cell performance, and projections of future works.